1999
DOI: 10.1121/1.427180
|View full text |Cite
|
Sign up to set email alerts
|

Auditory localization of nearby sources. Head-related transfer functions

Abstract: Although researchers have long recognized the unique properties of the head-related transfer function (HRTF) for nearby sources (within 1 m of the listener's head), virtually all of the HRTF measurements described in the literature have focused on source locations 1 m or farther from the listener. In this study, HRTFs for sources at distances from 0.12 to 1 m were calculated using a rigid-sphere model of the head and measured using a Knowles Electronic Manikin for Acoustic Research (KEMAR) and an acoustic poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
239
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 307 publications
(258 citation statements)
references
References 18 publications
11
239
1
1
Order By: Relevance
“…However, ILDs can occur, at least for the human listeners: Several studies have shown that also at frequencies below 1 kHz, ILDs of up to 5 dB are generated at sound-source distances around 1 m (Brungart and Rabinowitz 1999;Kuwada et al 2010). Even though both cues were shown to be present in low-frequency sounds, a recent study of Macpherson and Middlebrooks (2002) showed that listeners judged ITDs as the prominent cue to determine the azimuthal position of a low-frequency signal.…”
Section: Fig 5 Localization Thresholds and Resultant Release From Mmentioning
confidence: 99%
“…However, ILDs can occur, at least for the human listeners: Several studies have shown that also at frequencies below 1 kHz, ILDs of up to 5 dB are generated at sound-source distances around 1 m (Brungart and Rabinowitz 1999;Kuwada et al 2010). Even though both cues were shown to be present in low-frequency sounds, a recent study of Macpherson and Middlebrooks (2002) showed that listeners judged ITDs as the prominent cue to determine the azimuthal position of a low-frequency signal.…”
Section: Fig 5 Localization Thresholds and Resultant Release From Mmentioning
confidence: 99%
“…of ILDs (35), which is arguably a prominent auditory distance cue (18,29,36). Further experiments and/or modeling analyses will be required to clarify the perceptual weighting of these potential distance cues.…”
Section: Spectral Contrast Manipulation Affected Auditory Distance Pementioning
confidence: 99%
“…Implicitly, we have suggested that listeners can use a disparity between interaural time differences and ILDs to recognize that a source is not facing them directly. We realize that such disparity has also been proposed as a cue to source elevation (Searle, et al, 1975) as well as to the distance of nearby sources (Brungart, 1999;Brungart and Rabinowitz, 1999). Furthermore, we acknowledge that there are a host of other possible cues that listeners may use to perceive facing angle.…”
Section: Resultsmentioning
confidence: 99%